Development of [ 18 F]AmBF 3 Tetrazine for Radiolabeling of Peptides: Preclinical Evaluation and PET Imaging of [ 18 F]AmBF 3 -PEG 7 -Tyr 3 -Octreotide in an AR42J Pancreatic Carcinoma Model - Otaru, Sofia; Paulus, Andreas; Imlimthan, Surachet; Kuurne, Iida; Virtanen, Helena; Liljenbäck, Heidi; Tolvanen, Tuula; Auchynnikava, Tatsiana; Roivainen, Anne; Helariutta, Kerttuli; Sarparanta, Mirkka; Airaksinen, Anu J. (Bioconjugate chemistry, 2022)
Radiolabeled peptides have emerged as highly specific agents for targeting receptors expressed in tumors for therapeutic and diagnostic purposes. Peptides developed for positron emission tomography (PET) are typically radiolabeled using prosthetic groups or bifunctional chelators for fast "kit-like" incorporation of the radionuclide into the structure. A novel [ F]alkylammoniomethyltrifluoroborate ([ F]AmBF ) tetrazine (Tz), [ F]AmBF -Tz, was developed for the [ F]fluorination of -cyclooctene (TCO)-modified biomolecules using Tyr -octreotides (TOCs) as model peptides. [ F]AmBF -Tz (A = 15.4 ± 9.2 GBq/μmol, = 14) was evaluated in healthy mice by biodistribution and PET/computed tomography (CT), where the radiolabel in the prosthetic group was found stable , indicated by the low bone uptake in tibia (0.4 ± 0.1% ID/g, = 270 min). TCO-TOCs tailored with polyethylene glycol (PEG) linkers were radiolabeled with [ F]AmBF -Tz, forming two new tracers, [ F]AmBF -PEG -TOC (A = 2.8 ± 1.8 GBq/μmol, = 3) and [ F]AmBF -PEG -TOC (A of 6.0 ± 3.4 GBq/μmol, = 13), which were evaluated by cell uptake studies and biodistribution in subcutaneous AR42J rat pancreatic carcinoma tumor-bearing nude mice. The tracer demonstrating superior behavior , the [ F]AmBF -PEG -TOC, was further evaluated with PET/CT, where the tracer provided clear tumor visualization (SUV = 1.01 ± 0.07, SUV = 0.76 ± 0.04) at 25 min post injection. The novel AmBF -Tz demonstrated that it offers potential as a prosthetic group for rapid radiolabeling of biomolecules in mild conditions using bioorthogonal chemistry.